ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC PADA PT. BANK MANDIRI (PERSERO), TBK. PERIODE TAHUN 2017-2020 - Nabilah Thifaaly Putri (2021)
The purpose of this study aims to determine the health level of bank at PT. Bank Mandiri (Persero), Tbk. in period 2017-2020 with the method contained in the Financial Services Authority Regulation No. 8/PJOK 03/2014, namely RGEC (Risk Profile, Good Corprate Governance, Earning, and Capital). The method used in this study is a qualitative method and an approach using descriptive methods. This type of method is used with the aim of obtaining information about the health of the bank based on data obtained from the financial statements of PT. Bank Mandiri (Persero), Tbk. year 2017-2020. The results of the assessment of the health level of PT. Bank Mandiri (Persero), Tbk. 2017-2020, which is in accordance with the assessment determined by the Financial Services Authority. In 2017-2020 the financial ratios of PT. Bank Mandiri (Persero), Tbk. overall can be said to be stable with a healthy predicate Keywords: Bank Soundness Level, RGEC